Energy Dissipation and Vibration Control: Modeling, Algorithm and Devices - Gangbing Song (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2018)
While the study of vibration and energy dissipation is one of the oldest topics in engineering, it also encompasses some of the most exciting engineering problems of our time. From the exploration of deep sub-sea reservoirs to the stabilization of spacecraft in orbit, the problem of vibration control is ever present. To a certain extent, the technological progress of our civilization is tied to our understanding of vibration, and advances made in this field will only allow us to reach greater horizons. This book attempts to capture a glimpse of our current progress in this field by showcasing over 15 chapters of cutting-edge research performed by world leading experts in vibration control and energy dissipation. We hope the reader will be able to gain an understanding of the state-of-the-art, and if possible, be inspired by the vast scope and possibilities offered by the field of vibration control and energy dissipation.